Recurrent nodular fasciitis of the external auditory canal: an intriguing diagnosis - Anto, Ronald; Sampathkumar, Raghunandhan; Kameswaran, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
The external auditory canal can sometimes present with unique pathology since it is a vibrant environment possessing a variety of anaomical structures including bone, cartilage, skin, ceruminous glands and fibro-collagen tissues. Nodular fasciitis is an intriguing entity which rarely presents in the external ear canal as a growth. The diagnosis is made only through histopathological confirmation after ruling out similar benign or malignant lesions including ceruminoma, granuloma or carcinoma. Fasciitis being of fibrous origin has propensity to recur wherein management becomes more challenging. This is a clinical profile of a case of recurrent nodular fasciitis which was surgically managed and followed up with no further recurrence.